The Effect of Thallium on the Rate of Extraction of Gold from Pyrites Calcine (The Australasian Institute of Mining and Metallurgy, 1964)
The addition of a thallous salt to the cyanide leach of a calcined pyritic concentrate causes a marked increase in the"rate of extraction of gold. This probably is due to the activation of passive gold by.th,e. thallous ions'.''Lea'd, bismuth, and mercury salts, which should produce ' a, similai effect, fail to do so. It is postulated that'this latter result, together with'the reprecipitation of silver at low cyanide levels, is due to the presence of soluble sulphide. The use of thallous salts to reduce leaching time is discussed briefly.